FORMALIN PIGMENT DEPOSITION IN THE RENAL TUBULES IN KETOACIDOSIS. (February 2015) - Zhou, Chong; Gilbert, John D.; Yool, Andrea; Byard, Roger W.
Abstract : Aim: To assess whether formalin pigment deposition may be a useful marker for ketoacidotic basal vacuoles in putrefied kidneys. Methods: Case files were retrospectively reviewed at Forensic Science SA, Adelaide, South Australia, over a six-year period for cases of ketoacidosis. A control group matched for postmortem interval was selected. Cases were graded from 0–3+ for basal tubular epithelial cell formalin pigment deposition and also for autolytic/putrefactive changes. Results: There were 31 cases of ketoacidosis (age range 21–80 years; mean 50.9 years; M:F ratio 2:1). The post-mortem interval was 1–12 days (mean 4.5 days). Basal pigment surrounding vacuoles occurred in 16 cases (51.6%). No staining was demonstrated in control cases. Discussion: Basal vacuolisation of renal tubular epithelial cells is associated with ketoacidosis, but its presence may be obscured by autolysis. Therefore, other methods of identifying this change at autopsy would be useful. Basal formalin pigment deposition was found to be a highly specific (100%), but not a particularly sensitive marker of ketoacidosis (found in 51.6% of cases). As pigment deposition was easily identifiable after recognisable cellular morphology had been lost, this artefact of fixation can be very useful in identifying possible ketoacidosis in decomposed bodies with compromised histology.